Long-Term (More than 5 Years) Outcomes of Incisional Hernia Mesh Repair: A Literature Review - Jurgutavičius, Povilas; Varanauskas, Gintaras; Brimas, Gintautas (Lietuvos chirurgija, 2024)
Introduction. Postoperative hernias occur in 10–15% of patients. Considering the increase in the incidence of complications with the number of operations it is crucial to choose the optimal surgical technique in order to control the complications rate. This literature review summarizes previous studies on the treatment of postoperative hernias with mesh, comparing complication and recurrence rates according to surgical technique and mesh position. Methods. A thorough search was conducted on the PubMed database to retrieve literature on recurrence, chronic pain, haematoma, seroma, and surgical site infections rates. The results were meticulously summarised and used to confidently compare open and laparoscopic surgical techniques, as well as “sublay” and “onlay/inlay” mesh positions in more than 5-year follow-up. Results. The analysis was conducted on five publications that met the selection criteria. The results showed that laparoscopically treated hernias had lower recurrence and chronic pain rates, but more frequent haematomas. The presence of wound infections, BMI >30, treatment of recurrent postoperative hernias, multiple fascia lesions, enterotomy, larger abdominal wall defect and longer operative time were observed to be associated with higher recurrence rates. The position of the sublay mesh is associated with less frequent seromas, surgical infections, and recurrence compared to the onlay/inlay position. Studies have reported the superiority of large-pore lightweight polypropylene multifilament mesh over the same heavyweight mesh in managing postoperative hernias. Lightweight mesh is linked to a lower risk of hernia recurrence and higher compliance with the abdominal wall. Conclusion. Laparoscopic surgery is associated with lower rates of recurrence and chronic pain, but a higher frequency of haematomas. The sublay mesh position is associated with lower rates of seromas, surgical infections, and recurrence.
Keywords: incisional hernia; mesh repair; long-term results; laparoscopic surgery; open surgery